1996
DOI: 10.1046/j.1365-3083.1996.d01-14.x
|View full text |Cite
|
Sign up to set email alerts
|

Histaminergic Regulation of Natural Killer Cell‐Mediated Clearance of Tumour Cells in Mice

Abstract: Treatment of Swiss albino mice with histamine enhanced the clearance of natural killer (NK)-cell sensitive YAC-1 lymphoma and B16/F10 melanoma cells from lung tissue in vivo, but did not affect the elimination of NK-cell-insensitive P815 mastocytoma cells. The effect of histamine was apparently mediated by H2-type histamine receptors (H2R) since it was blocked by ranitidine, and H2R antagonist. Histamine did not affect clearance of tumour cells in animals depleted of NK cells in vivo by treatment with antibodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0

Year Published

1997
1997
2006
2006

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(20 citation statements)
references
References 22 publications
1
19
0
Order By: Relevance
“…Our data support a novel treatment strategy involving the blocking of phagocyte-generated ROS by histamine, thereby protecting NK and T cells from apoptosis and, thus, synergising with IL-2 in inducing NK-and T-cell activation Asea et al, 1996;Hansson et al, 1999). Clearly, with regard to the 'good guys', treatment with IL-2/HDC resulted in significantly higher numbers of intratumoural NK and CD8 þ T cells during treatment compared with baseline.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Our data support a novel treatment strategy involving the blocking of phagocyte-generated ROS by histamine, thereby protecting NK and T cells from apoptosis and, thus, synergising with IL-2 in inducing NK-and T-cell activation Asea et al, 1996;Hansson et al, 1999). Clearly, with regard to the 'good guys', treatment with IL-2/HDC resulted in significantly higher numbers of intratumoural NK and CD8 þ T cells during treatment compared with baseline.…”
Section: Discussionsupporting
confidence: 59%
“…Targeting NADPH-oxidase through binding to the H 2 -receptor on monocytes (Hellstrand and Hermodsson, 1986) and neutrophils (Betten et al, 2003), HDC specifically blocks the formation and release of hydrogen peroxide (H 2 O 2 ), thereby protecting NK and T cells from oxygen radical-induced inhibition and apoptosis (Hellstrand et al, 1994). Thus, NK and T cells remain viable and responsive to interleukin-2 (IL-2) Asea et al, 1996). IL-2 has no direct impact on tumour cells (Rosenberg, 2001) but requires NK and T-cells for tumourlysis (Donskov et al, 2002a(Donskov et al, , 2004a.…”
mentioning
confidence: 99%
“…Thereby, histamine may synergize with IL-2 to induce NK cell-mediated killing of a variety of cultured tumour cells in vitro (Hellstrand and Hermodsson, 1990;Hellstrand et al, 1994b). Treatment of mice with histamine also enhances the IL-2-induced activation of NK cells in vivo (Asea et al, 1996) and addition of histamine to conventional IL-2 therapy has shown initial promise in patients with metastatic melanoma (Hellstrand et al, 1994a) and acute myelogenous leukaemia (Brune and Hellstrand, 1996).…”
mentioning
confidence: 99%
“…Clearance of YAC-1 cells was significantly enhanced in animals pretreated with histamine, acting via H2R, and reduced by ranitidine and other H2R antagonists (such as cimetidine, tiotidine, and famotidine). The effect of histamine on lung clearance of YAC-1-cells was completely abrogated in animals depleted of NK cells in vivo (22,31).…”
Section: Histamine and Cytokines In Experimental Neoplasiamentioning
confidence: 99%
“…It was found that the addition of histamine effectively potentiated the anti-metastatic effect produced by IL-2 or IFN-h in B16 melanoma, and that treatment with histamine and IL-2 as well as with histamine and IFN-h apparently synergistically augmented the NK-cell-mediated killing of YAC-1 lymphoma cells in vivo (22,31).…”
Section: Histamine and Cytokines In Experimental Neoplasiamentioning
confidence: 99%